Current Tobacco Smoking Prevalence Among Iranian Population: A Closer Look at the STEPS Surveys - Mohammad-Reza Sohrabi; Mohsen Abbasi-Kangevari; Ali-Asghar Kolahi (Frontiers Media S.A., 2020)
Objectives: To determine the current tobacco smoking prevalence among Iranian adults, its geographical distribution in 2011, 2016, and time trend during 2004-2016.Methods: We conducted a pooled analysis of the published reports of 2004, 2007, 2008, 2009, and the data of 2011 and 2016 of the STEPwise approach to chronic disease risk-factor surveillance (STEPS) surveys.Results: The prevalence of current tobacco smoking and current daily cigarette smoking in 2016 was 14.1 and 9.7%, respectively. Only 0.2% of participants smoked water-pipe. Current tobacco smoking prevalence remained unchanged during 2004-2016 for both men and women. The prevalence of passive smoking at home or workplace was 27.4%. Current tobacco smoking prevalence and current daily cigarette smoking was significantly lower among women than men. Current tobacco smoking prevalence showed a geographical pattern throughout the country. In both 2011 and 2016, current tobacco smoking prevalence was higher among men who lived in the western provinces, especially the north-west, than those who lived in the eastern and southern provinces.Conclusions: The current tobacco smoking prevalence among Iranian population has not changed significantly during 2004-2016 and does not conform to the international guidelines. Therefore, it remains crucial yet challenging that effective nationwide policies be implemented to reduce the use of tobacco products. One cannot hope for any reductions in smoking prevalence until a cocktail of interventions are built around strong commitment to government policy.